Conflict of interests driven by pharmaceutical incentivisation: risks to the medical fraternity in Pakistan - Muhammad Naveed Noor; Afifah Rahman-Shepherd; Amna Rehana Siddiqui (Journal of the Pakistan Medical Association, 2023)
Conflict of interest (COI) in medical practice, and how it affects healthcare delivery and quality, is a poorly studied issue in Pakistan. COI can broadly be defined as a situation that arises when the opportunity for personal gain takes primacy over an individual’s professional responsibilities.1 In medicine, trust is the cornerstone of the doctor-patient relationship. Doctors hold an authoritative position based on their knowledge and expertise and are entrusted by the healthcare system and patients to put the patients’ best interests first. This means that to maintain trust, not only doctors are required to appropriately diagnose, treat and/or manage patients’ illnesses, but also consider their social and financial circumstances. In this editorial, we draw attention to a prime example of how COI manifests in medical practice as a result of the interactions between doctors and pharmaceutical sales representatives (PSRs). While PSRs are a source of knowledge on existing and new pharmaceutical products, this relationship can turn into an apparatus of financial corruption, when, in their efforts to maximise profits, PSRs incentivise doctors for prescribing. We refer to this as incentive-linked prescribing (ILP) whereby doctors accept some form of incentive in exchange for prescribing to meet pharmaceutical sales targets, without considering the added financial burden on patients and adverse health outcomes. In 2021, the Drug Regulatory Authority of Pakistan (DRAP) published rules by which pharmaceutical companies are prohibited to offer incentives to doctors for prescriptions, however, these rules are poorly enforced.2 The absence of concrete legislation, clear-cut guidelines, sound monitoring, and regulation mechanism paves the way for the establishment of the unethical profit-driven relationship between doctors and the pharmaceutical industry. Consequences of ILP to patients, doctors, and the healthcare system There is growing attention to ILP and its consequences to medical practice and public health in Pakistan. Research has shed light on the well-entrenched influence of PSRs on physicians prescribing practices.3 This level of influence is achieved with the help of incentives, which foster dependent relationships between physicians and the pharmaceutical industry. Alarmingly, much of the research concludes that ILP has become normalised within the medical fraternity and how they interact with pharmaceutical companies.3,4 ILP can lead to several negative consequences for patients, doctors, and the healthcare system, and it is critical that doctors are made aware of these consequences. Patients may be aware of the unethical profit-driven relationship between doctors and pharmaceutical companies, and for this reason, lose trust in doctors. Doctors may prescribe most costly and/or unnecessary medications than what would otherwise have been prescribed. This can put patients under additional financial pressure and subject them to potential adverse health outcomes. Indeed, ILP is one of the largest contributors to the consumption of antibiotics in Pakistan, in addition to over-the-counter medications.5 The abuse and misuse of antibiotics is the leading reason for antimicrobial resistance (AMR) worldwide, which is one of the top ten threats to global health and is estimated to cause ten million deaths each year by 2030.6 These consequences have significant negative implications for the healthcare system, in terms of burden of disease, financing, and quality of care provided. Continued.....